Shell Eco-Marathon Fuel Consumption Engine Map - Muhamad Fikri, Jaafar (Universiti Sains Malaysia, 2022)
The Shell Eco-Marathon Fuel Consumption Engine Map is a study to discover the operating profile of an engine that was used as a drivetrain in the Shell Eco-Marathon Challenge. As the participant, the USM team is required to build a fuel-efficient vehicle prototype that can be driven further while consuming the least amount of fuel. A Honda 110 cc engine has been chosen to be used as the drivetrain for the prototype vehicle. However, technical information regarding the engine operating profile is quite limited causing difficulties in optimizing the prototype vehicle for the best fuel mileage. To optimize the fuel consumption of the engine, the engine must be operated in its ‘sweet spot’ of the fuel consumption map most of the time. The main objective of this project is to discover fuel consumption, brake-specific fuel consumption, and brake thermal efficiency for that particular engine. Knowing these parameters is important as it can be used to find the engine map optimum point where the engine is capable to achieve the highest thermal efficiency. This project involves engine modification, fabrication, experiments, and programming. Before the experiment can be conducted, an automatic centrifugal clutch delete modification is performed toward the engine to minimize the mechanical losses during dynamometer engine testing. A few measuring instruments were fabricated to make the data collection process easier. The dynamometer engine testing is performed by utilizing an Eddy Current Dynamometer that is available at the Automotive Laboratory, School of Mechanical Engineering, USM. During the experiments, the performance and fuel consumption of the engine was observed at different engine speeds and loads. The experiment’s result shows that the engine was capable of producing a maximum torque of 7.31 Nm at 5500 RPM and maximum brake power of 5.33 kW at 7500 RPM. The efficient operating zone of the engine occurred at the lowest brake-specific fuel consumption was 347.3 g/kWh which was recorded at 5000 RPM with a 5.42 Nm load. The highest thermal efficiency achieved by the engine is 23.87%. MATLAB programming software was used to construct a 3-D graph of fuel consumption map, brake-specific fuel consumption, and brake thermal efficiency for that particular engine. The finding of the engine operating profile is important as it can be used to optimize the transmission drive ratio and driving strategy of the USM team Shell Eco-Marathon prototype vehicle.